2020
DOI: 10.3390/s20226580
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Water Leaving Reflectance Using a Digital Camera Based on Multiple Reflectance Reference Cards

Abstract: With the development of citizen science, digital cameras and smartphones are increasingly utilized in water quality monitoring. The smartphone application HydroColor quantitatively retrieves water quality parameters from digital images. HydroColor assumes a linear relationship between the digital pixel number (DN) and incident radiance and applies a grey reference card to derive water leaving reflectance. However, image DNs change with incident light brightness non-linearly, according to a power function. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Validation campaigns have consistently found the radiance, R rs in the RGB bands, and hue angle from consumer cameras to be wellcorrelated with reference instruments, but often with a wide dispersion and a significant bias. For R rs , the mean difference between smartphone and reference match-up data is typically ≥ 0.003 sr −1 or ≥ 30%, but varies wildly between studies (Leeuw and Boss, 2018;Yang et al, 2018;Gao et al, 2020Gao et al, , 2022). As an extreme example, Malthus et al (2020) found no correlation at all between HydroColor and reference R rs data, albeit under challenging observing conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Validation campaigns have consistently found the radiance, R rs in the RGB bands, and hue angle from consumer cameras to be wellcorrelated with reference instruments, but often with a wide dispersion and a significant bias. For R rs , the mean difference between smartphone and reference match-up data is typically ≥ 0.003 sr −1 or ≥ 30%, but varies wildly between studies (Leeuw and Boss, 2018;Yang et al, 2018;Gao et al, 2020Gao et al, , 2022). As an extreme example, Malthus et al (2020) found no correlation at all between HydroColor and reference R rs data, albeit under challenging observing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, in a process termed gamma correction or gamma compression, the radiance is scaled by a power law. The nonlinearity of JPEG data is a significant contributor to the uncertainty in R rs obtained from consumer cameras and apps such as HydroColor (Burggraaff et al, 2019;Gao et al, 2020;Malthus et al, 2020). Some approaches, including WACODI, attempt to correct for nonlinearity through an inverse gamma correction (Novoa et al, 2015;Gao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Location sensors (GPS) and cameras on board the mobile devices equip the citizens to collect geotagged data and store them. The use of smartphones and digital cameras in citizen science programmes are improving day by day, an example of which is the mobile application HydroColor that derives water leaving reflectance from digital images (Gao et al, 2020). Most of the citizen science programmes in hydrology from 2001 to 2018 seem to have focused on the monitoring of water quality (Njue et al, 2019), probably due to the increased global awareness on the deterioration of water quality plus the availability of low-cost kits to measure basic water quality variables.…”
Section: Introductionmentioning
confidence: 99%
“…Pitarch et al [ 9 ] has presented 15 years of the evaluation of hue angle and FUI through of oceanic waters on a global scale. Gao et al [ 10 ] developed a method to estimate water leaving reflectance via digital imagery.…”
Section: Introductionmentioning
confidence: 99%